Age-specific reference ranges are needed to interpret serum methylmalonic acid concentrations in the US population. Issue 1 (25th May 2019) - Mineva, Ekaterina M; Sternberg, Maya R; Zhang, Mindy; Aoki, Yutaka; Storandt, Renee; Bailey, Regan L; Pfeiffer, Christine M
ABSTRACT: Background: Serum vitamin B-12 is measured to evaluate vitamin B-12 status. Serum methylmalonic acid (MMA) is a specific functional indicator of vitamin B-12 status; however, concentrations increase with impaired renal function. Objective: The aim of this study was to describe the distribution of serum vitamin B-12 and MMA in US adults, and estimate age-specific reference intervals for serum MMA in a healthy subpopulation with replete vitamin B-12 status and normal renal function. Methods: We examined cross-sectional data for serum vitamin B-12 and MMA in adults participating in the NHANES from 2011 to 2014. Vitamin B-12 was measured by electrochemiluminescence assay and MMA by isotope-dilution liquid chromatography–tandem mass spectrometry. Results: In both bivariate and multivariate analyses, age, race/Hispanic origin, and vitamin B-12 supplement use were generally significantly associated with serum vitamin B-12 and MMA concentrations. Serum MMA concentrations increased with age, particularly in persons aged ≥70 y. Non-Hispanic white persons had lower vitamin B-12 and higher MMA concentrations than non-Hispanic black persons. Shorter fasting times and impaired renal function were significantly associated with higher serum MMA concentrations, but not with serum vitamin B-12 concentrations after controlling for covariates. The central 95% reference intervals for serum vitamin B-12 and MMA concentrations were widest for persons aged ≥70 y compared with younger age groups. Compared with the overall population, the central 95% reference intervals for serum MMA concentrations were considerably narrower for a vitamin B-12–replete subpopulation with normal renal function, but still age-dependent. Serum vitamin B-12 showed little, whereas serum MMA showed notable, increases with impaired renal function. Conclusions: The higher serum MMA concentrations throughout the entire distribution in older persons (especially persons aged ≥70 y) who are vitamin B-12–replete and have normal renal function indicate the need for age-specific MMA reference intervals to better interpret vitamin B-12 status in epidemiologic research.